2020
DOI: 10.1093/cid/ciaa1180
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 (COVID-19) in Americans Aboard theDiamond PrincessCruise Ship

Abstract: Background The Diamond Princess cruise ship was the site of a large outbreak of coronavirus disease 2019 (COVID-19). Of 437 Americans and their travel companions on the ship, 114 (26%) tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Methods We interviewed 229 American passengers and crew after disembarkation following a ship-based quarantine to identify risk factors for infection and characterize transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 19 publications
1
71
0
1
Order By: Relevance
“…Previous studies have suggested the heterogeneity in the cases on different decks and locations due to different transmission modes (Azimi et al 2020;Fang et al 2020;Plucinski et al 2020;Yamagishi et al 2020b). The fomite and aerosol transmission (van Doremalen et al 2020;Mallapaty 2020;Mizumoto and Cowell 2020;Nakazawa et al 2020), and meteorological factors (Cheng and Wang-Li 2019;Hsiao et al 2020;Lin et al 2020;Pang et al 2020;Pani et al 2020) have been reported to make respective contributions to the spread of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have suggested the heterogeneity in the cases on different decks and locations due to different transmission modes (Azimi et al 2020;Fang et al 2020;Plucinski et al 2020;Yamagishi et al 2020b). The fomite and aerosol transmission (van Doremalen et al 2020;Mallapaty 2020;Mizumoto and Cowell 2020;Nakazawa et al 2020), and meteorological factors (Cheng and Wang-Li 2019;Hsiao et al 2020;Lin et al 2020;Pang et al 2020;Pani et al 2020) have been reported to make respective contributions to the spread of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 97%
“…Overall, 27 studies were identified referring to the Diamond Princess. Eleven studies gave a descriptive epidemiology report of the outbreak of SARS-CoV-2 on the cruise ship [39][40][41][42][43][44][45][46][47][48][49] analyzing, e.g., the proportion of asymptomatic cases [39,[42][43][44][45][46][47][48][49]. Seven studies analyzed clinical outcomes or clinical courses [39,45,[50][51][52][53][54] e.g., with a special focus on conjunctivitis [53], lung opacities and airway abnormalities [39,52] or single patients [51].…”
Section: Study Characteristcsmentioning
confidence: 99%
“…In the outbreak cluster, we observed that the asymptomatic carriers and minimally symptomatic patients (without fever) accounted for 35.7% and 28.6% of the cases (Table 1), respectively, which is consistent with previous studies. 16,17,24,25 It is worth noting that the four minimally symptomatic patients did not realize their SARS-CoV-2 infection and were missed by mandatory temperature checks. Therefore, when discussing prevention and control strategies for COVID-19, the minimally symptomatic carriers should be managed the same as asymptomatic cases.…”
Section: Discussionmentioning
confidence: 99%